Near-threshold, steady state interaction of oxygen ions with transition metals: Sputtering and radiation enhanced diffusion - Phadke, Parikshit; Stilhano Vilas Boas, Cristiane R.; Sturm, Jacobus M.; van de Kruijs, Robbert W.E.; Bijkerk, Fred (Applied surface science, 2020)
[Display omitted] •Measured steady state sputter yields for Mo, Ru, Pd, W targets under oxygen ion bombardment at energy range 50–500 eV.•Ion induced oxides have similar states as atomic O exposed metals but with larger oxide thickness.•Oxide thickness from ions larger than range of ion transport from TRIDYN simulations.•External diffusion algorithm models diffusive transport of oxygen freed from oxide upon ion bombardment.•Radiation enhanced diffusion from ion bombardment explains oxide thicknesses formed at near-threshold ion energies. Transition metals used in semiconductor, photolithography and fusion applications interact with low energy oxygen ions. Understanding erosion, the nature of the formed oxide and depth of oxygen transport is necessary in mitigating unexpected performance of sensors, optics or plasma facing components. Oxide formation is governed by both the ion–target combination and the incident ion energy. We study the interaction of the transition metals molybdenum, ruthenium, palladium and tungsten, with oxygen ions in the energy region of 50–500 eV. Near-threshold sputtering of metals was experimentally measured and compared to predictions by the Monte Carlo code TRIDYN. Compositional changes and oxide thicknesses following sputtering were measured using Angle resolved X-ray photoelectron spectroscopy and subsequently compared to limiting oxide formed by atomic oxygen exposures. Sputter yields in some cases (ruthenium) were found to be sensitive to ion beam impurities such as ozone (<1% of background gas) leading to chemical sputtering. Ion induced oxide thicknesses (for molybdenum and tungsten) were found to be larger than those predicted by ballistic transport where sputtering is balanced by implantation. It is hypothesized that radiation enhanced diffusion of free oxygen leads to thicker oxide films at low ion energies.